BANKS AND WAR AGAINST FINANCIAL CRIME IN NIGERIA DIGITAL PAYMENT SYSTEM (Journal of Global Accounting, 2024)
The study on banks and war against financial crime in Nigeria, primarily aimed at assessing the effectiveness of the banks’ security measures in fighting financial crimes in Nigerian digital payment system. Bi-monthly data of the entire Deposit Money Banks operating in Nigeria as at 2012-2021 computed from the extracts from NDIC annual reports (2013, 2017, 2019 and 2021) and CBN Statistics Database (2012-2020) were used. Auto regression Distributed Lag (ARDL) model estimation was utilized for data analysis/test of hypotheses. Findings disclosed that banks' security measures are partially effective in the fight against frauds and forgery in Nigeria’s digital banking system, as digital payment transactions (with the existing fraud prevention tools) through ATM and mobile phones have depressed the opportunity to commit fraud, while reverse is the case with POS transactions and internet banking. The study recommended among others that banks should install a good fraud linking software in all electronic payment channels with more focus on POS terminals and internet, which can aid the bank view relationships between transactions through identifiers like passwords, usernames, and others. This would help to disclose with relative certainty that a transaction may be fraudulent since the individual carrying out the transaction has previously carried out a confirmed fraudulent transaction, thereby facilitating fraud prevention..
Keywords: Digital payment system; Financial Crime Fraud; Forgery; Security Measures; War